Housing in Portugal after the economic crisis: challenges for a new policy - Matos, Fátima Loureiro de (2019)
Housing is a central element of citizenship and the right to the city. In current society, apart from comprising a key element to achieving the minimum threshold of human needs - vital to survival -, housing has progressively been called on to fulfil a varied range of decisive requirements for the populations quality of life. In the last decade, with the economic crisis, difficulties in the access to housing have increased, housing condition have not improved and the segmentation of housing types by different social classes has deepened. In Portugal, notwithstanding the considerable improvements achieved prior to the economic crisis regarding the decrease of housing needs, there are still many problems of a structural nature that need to be overcome. At the same time, new challenges have arisen in the last decade, some deriving from the crisis itself, others from the continuation of existing tendencies (such as population ageing) or the appearance of new urban dynamics (namely the pressure of tourism on the housing market). In order to understand the challenges that Portugal faces in terms of housing, this chapter will explore the housing dynamics of the last decades and identify the current issues. It will start by analyzing the dynamic of the housing supply when facing a changing demand. Then, it will be discussed how this dynamic influences home ownership in the face of the decline of rental accommodations. This will be followed by an analysis of the state-led promotion of housing. Lastly, the challenges for a housing public policy will be identified.